Model Hubungan Self-esteem dan Outcome expectation dalam Memprediksi Minat Mengajar: Pendekatan Social Cognitive Career Theory - Kurniawan, Fedi; Isdiati, Erni Harlina (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to analyze the influence of self-esteem and outcome expectations on students’ interest in becoming teachers, with (CDSE) as a mediating variable within the framework of the Social Cognitive Career Theory (SCCT). The research addresses the declining interest of teacher education students in pursuing teaching professions and seeks to identify internal psychological mechanisms that shape teaching career intention.Method – Using a quantitative explanatory design, this study involved 83 students of Economic Education at Universitas Negeri Semarang (UNNES) selected through simple random sampling. Data were collected via standardized instruments adapted from Rosenberg (1965), Taylor & Betz (1983), Lent & Brown (2013), and McCoach et al. (2013). Mediation analysis was performed using regression with 5,000 bootstrap resampling and bias-corrected confidence intervals (95% CI) via PROCESS Macro v4.3 (Hayes, 2018).Findings – The results reveal that self-esteem significantly affects CDSE (? = 1.212, p < 0.001) but not teaching interest directly (? = 0.116, p = 0.399). Conversely, outcome expectations influence both CDSE (? = 0.905, p < 0.001) and teaching interest (? = 0.605, p < 0.001). CDSE fully mediates the relationship between self-esteem and teaching interest, and partially mediates that between outcome expectations and teaching interest (R² = 0.89–0.92). Research Implications – The findings extend SCCT by confirming the full mediation of CDSE between self-esteem and teaching interest in Indonesian pre-service teachers. Policy implications suggest that teacher education curricula should integrate structured career efficacy training and address the economic stigma surrounding teaching by improving teacher welfare and career incentives. Future longitudinal or cross-institutional research is recommended to examine the development of CDSE and teaching interest across different teacher education institutions.